2018
DOI: 10.1242/dev.166215
|View full text |Cite
|
Sign up to set email alerts
|

Neural differentiation, selection and transcriptomic profiling of human neuromesodermal progenitors-like cells in vitro

Abstract: Robust protocols for directed differentiation of human pluripotent cells are required to determine whether mechanisms operating in model organisms are relevant to our own development. Recent work in vertebrate embryos has identified neuromesodermal progenitors as a bipotent cell population that contributes to paraxial mesoderm and spinal cord. However, precise protocols for in vitro differentiation of human spinal cord progenitors are lacking. Informed by signalling in amniote embryos, we show here that transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 67 publications
9
84
0
Order By: Relevance
“…According to this idea, NMPs contribute to trunk neurons, such as spinal motor neurons, during body/tail elongation. Generation and characterization of trunk neural cell types through NMPs is a topic of wide interest with the potential for therapeutic application (Gouti et al, 2015;Verrier et al, 2018). Recent reports demonstrated that manipulation of retinoic acid, hedgehog and BMP/TGFβ signaling can alter neural differentiation from NMPs (Cunningham et al, 2016;Gouti et al, 2014;Lippmann et al, 2015;Verrier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this idea, NMPs contribute to trunk neurons, such as spinal motor neurons, during body/tail elongation. Generation and characterization of trunk neural cell types through NMPs is a topic of wide interest with the potential for therapeutic application (Gouti et al, 2015;Verrier et al, 2018). Recent reports demonstrated that manipulation of retinoic acid, hedgehog and BMP/TGFβ signaling can alter neural differentiation from NMPs (Cunningham et al, 2016;Gouti et al, 2014;Lippmann et al, 2015;Verrier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Generation and characterization of trunk neural cell types through NMPs is a topic of wide interest with the potential for therapeutic application (Gouti et al, 2015;Verrier et al, 2018). Recent reports demonstrated that manipulation of retinoic acid, hedgehog and BMP/TGFβ signaling can alter neural differentiation from NMPs (Cunningham et al, 2016;Gouti et al, 2014;Lippmann et al, 2015;Verrier et al, 2018). Therefore, accelerated neural patterning and differentiation in the absence of Sall4 in NMPs and their descendants offer a possibility of manipulating neural differentiation in vitro through regulating functions of Sall4 in combination with these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that the use of human ESCs, with the slower progression to neural progenitor cell identity, would provide a better temporal resolution of mechanisms mediating neural differentiation. To this end, we directed the differentiation of human ESCs towards spinal cord [13, 64] (Figure 2A). This regime involved the generation of NMP-like cells on day 3 (NMP-L D3), characterised by the co-expression of BRA and SOX2 and their differentiation into PAX6 expressing neural progenitors by day 8 (NP D8), which also transcribed the known PRC target HOXD11 (Figures B-B’’’).…”
Section: Resultsmentioning
confidence: 99%
“…While the transcriptomes of the neural stem zones and of the putative neuromesodermal precursors have been explored (Gouti et al, 2017;Verrier et al, 2018), the mesodermal stem zone is poorly characterised. As a prerequisite to assess the molecular identity of cells in posterior stem zones in functional experiments, we first sought to identify a specific molecular identity of MSZ, distinct from both the surrounding neural plate and the more caudal PS that continues to gastrulate.…”
Section: A Unique Molecular Profile Of the Mesodermal Stem Zonementioning
confidence: 99%